Liver enzyme abnormalities in taking traditional herbal medicine in Korea: A retrospective large sample cohort study of musculoskeletal disorder patients. (1st July 2015) - Lee, Jinho; Shin, Joon-Shik; Kim, Me-riong; Byun, Jang-Hoon; Lee, Seung-Yeol; Shin, Ye-sle; Kim, Hyejin; Byung Park, Ki; Shin, Byung-Cheul; Lee, Myeong Soo; Ha, In-Hyuk
Abstract: Ethnopharmacological relevance: The objective of this study is to report the incidence of liver injury from herbal medicine in musculoskeletal disease patients as large-scale studies are scarce. Considering that herbal medicine is frequently used in patients irrespective of liver function in Korea, we investigated the prevalence of liver injury by liver function test results in musculoskeletal disease patients. Materials and methods: Of 32675 inpatients taking herbal medicine at 7 locations of a Korean medicine hospital between 2005 and 2013, we screened for liver injury in 6894 patients with liver function tests (LFTs) at admission and discharge. LFTs included t-bilirubin, AST, ALT, and ALP. Liver injury at discharge was assessed by LFT result classifications at admission (liver injury, liver function abnormality, and normal liver function). In analyses for risk factors of liver injury at discharge, we adjusted for age, sex, length of stay, conventional medicine intake, HBs antigen/antibody, and liver function at admission. Results: A total 354 patients (prevalence 5.1%) had liver injury at admission, and 217 (3.1%) at discharge. Of the 354 patients with liver injury at admission, only 9 showed a clinically significant increase after herbal medicine intake, and 225 returned to within normal range or showed significant liver function recovery. Out of 4769 patients with normal liver function at admission, 27 (0.6%) had liver injury at discharge. In multivariate analyses for risk factors, younger age, liver function abnormality at admission, and HBs antigen positive were associated with injury at discharge. Conclusions: The prevalence of liver injury in patients with normal liver function taking herbal medicine for musculoskeletal disease was low, and herbal medicine did not exacerbate liver injury in most patients with injury prior to intake. Graphical abstract: